(Re)collecting and (re)turning to Ourselves: Creative Feminist and Queer Praxes with Migrants in Adult Learning - Rodrigues, Nelesi; Entigar, Katherine E.; Balyasnikova, Natalia (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2025)
In this article, we share three moments of glow when restlessness, curiosity, and wonder punctuated their teaching with culturally and linguistically diverse migrant learners. The authors use these moments to sit with uncertainty and discomfort, feelings they consider crucial to adult learning and critical praxis. Each author’s moment of glow—which incorporates a reflection on practice, followed by a response from the other authors—explores how creative practice and feminist and queer praxes collaborate to uncover critical insights and possibilities in community learning with Venezuelan migrants, 2SLGBTQ+ and/or migrant community members, and older migrants. The authors offer this piece as an example of collaborative inquiry that enacts feminist imagination in times when many feel unprepared to engage with discomfort in our teaching practices.